Influence of biofortification with chitosan-iodine complexes on the phytochemical quality of jalapeño pepper fruits - Sangerman-Jarquín, Dora Ma.; Sariñana-Aldaco, Oscar; Lara-Reimers, Eduardo A.; Ortega-Ortíz, Hortensia; Márquez-Guerrero, Selene Y.; Preciado- Ramgel, Pablo (Ecosistemas y Recursos Agropecuarios, 2023)
The use of chitosan-iodine (Cs-I) complexes can be a good strategy to improve the nutraceutical quality and the concentration of I in the edible part of crops. The objective of this study was to evaluate the effects of biofortification via foliar of I in a complex with Cs on the nutraceutical quality of jalapeño pepper fruits. The treatments were the following: absolute control, 1% Cs and I complex (5, 10, 15, 15, 20, and 25 mg L–1) + 1% Cs. The application of the 15 mg L–1 complex of Cs-I improved the nutraceutical quality of the fruits, in contrast to the application of 1% Cs individually. In addition, as the dose of the Cs-I complex increases, the accumulation of I in the fruit increases. The use of the Cs-I complex is an alternative to modulate the nutraceutical quality and I content in jalapeño pepper fruits.
Keywords: Antioxidants; biostimulation; biopolymers; trace element